BUILDING THE REPUTATION OF PRIVATE UNIVERSITIES BASED ON LECTURER AND STUDENT RESEARCH PERFORMANCE - Anggarina, Paula Tjatoerwidya; Irawan, Agustinus Purna; Dewi, Fransisca Iriani Roesmala; Devotyasto, Mario (Graduate Program of Universitas Tarumanagara, 2023)
A good reputation is one of the important things in building the trust of all stakeholders in private universities. High level of trust from the community will have a positive impact on the operations of universities, especially for sustainability in the present and in the future. One of the important factors that need to be considered in building a reputation is the publication of research performance of lecturers and students through trusted media. This paper discusses how the reputation of universities is built through published works, both by lecturers and students individually and in the publication team. The method of discussion uses descriptive analysis accompanied by several case studies of the reputation building process. Based on this discussion, information and various steps needed to build a sustainable reputation through the performance of publications that are beneficial to the wider community can be concluded. Sustainable publications with high quality have a positive impact on the reputation of accreditation performance and university rankings which are one of the main factors to gain public trust.